Dynamics of factors underlying willingness to communicate in a second language. Issue 4 (3rd July 2020) - Syed, Hassan; Kuzborska, Irena
ABSTRACT: The present study was designed to explore the situational variables and their interaction determining the willingness to communicate (WTC) in English (L2) of six postgraduate business students in a university classroom in Pakistan. While much research has been undertaken to examine trait-like psychological antecedents, only a few studies have examined the nature of the interaction between situational variables affecting L2 WTC in a classroom context. Adopting the Dynamic Systems Theory (DST) framework, the present study utilised classroom observations, learners' diaries, stimulated recall interviews and biographic questionnaires to collect the data over 10 weeks. The study results showed that participants' L2 WTC emerged as a result of the complex, dynamic and non-linear interaction between contextual, psychological, linguistic and physiological factors. The current study reinforces the theoretical shift from positivist and process-oriented approaches towards DST. Pedagogically, this study strongly proposes pre-service and in-service teacher training for Pakistani English language teachers to understand the complex and fluctuating nature of L2 WTC and not misinterpret learners' silence as an unwillingness to communicate.